2020
DOI: 10.2188/jea.je20190152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intentional and Unintentional Injuries Among Chinese Children and Adolescents

Abstract: Background: The patterns and risk factors of intentional injuries compared to unintentional injuries among Chinese children and adolescents have not been examined in depth. This work comprehensively describes patterns of intentional injuries in China, for which little information has been previously published. Methods: All cases involving individuals 0-17 years old registered at emergency rooms and outpatient clinics were examined using data submitted to the National Injury Surveillance System from 2006 throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
2
28
1
3
Order By: Relevance
“…Categorizing injuries according to intention is commonplace in the literature and assumed to have utility for injury management and prevention. For instance, prevention approaches to intentional injuries often focus on characteristics of individuals and their behaviours, while unintentional prevention initiatives are more often concerned with how people, objects and environments interact [ 36 ]. It is nevertheless worth noting that some have questioned whether categorisation limits collaboration and advancement of prevention efforts, as the underlying motivations of individuals are not always clear-cut (e.g., some burns are intentional, as are some road injuries), and groups share many similar characteristics, including effective prevention approaches (see Section 4 on policy and interventions below) [ 37 ].…”
Section: Specific Injury Typesmentioning
confidence: 99%
“…Categorizing injuries according to intention is commonplace in the literature and assumed to have utility for injury management and prevention. For instance, prevention approaches to intentional injuries often focus on characteristics of individuals and their behaviours, while unintentional prevention initiatives are more often concerned with how people, objects and environments interact [ 36 ]. It is nevertheless worth noting that some have questioned whether categorisation limits collaboration and advancement of prevention efforts, as the underlying motivations of individuals are not always clear-cut (e.g., some burns are intentional, as are some road injuries), and groups share many similar characteristics, including effective prevention approaches (see Section 4 on policy and interventions below) [ 37 ].…”
Section: Specific Injury Typesmentioning
confidence: 99%
“… 17 , 19–21 Most of our KRI cases were reported to be accidental, similar to the results of the previous study in China by Yin et al, who showed that 95.1% of the reported injuries were unintentional. 22 However, these results were much higher, compared with those of a comparable study in the UK, where only 52% of the KRIs were unintentional. 4 This difference may have been secondary to the different knife carrying habits and the marked increase in knife-related crimes in the UK.…”
Section: Discussionmentioning
confidence: 72%
“…Each singular risk/protective categorical is accomplished by a statistical criterion (e.g. upper quartile of risk exposure = 1; all others = 0) and then summed together to form the risk/protective factors index [9,12,27,28]. The risk factor index (RFI) was computed by adding on 3 risk measures: SDQ ≥ 22 (1 point), IBC ≥ 17 (1 point), and PRH ≥ 18 (1 point).…”
Section: Risk and Protective Factor Indicesmentioning
confidence: 99%
“…In China, childhood unintentional injuries are more prominent in rural areas. The unintentional injury risk of death in rural areas was approximately 1.95 times that compare to urban areas of China [8,9]. In Chinese rural areas, there is a special group called left-behind children whose parents have left the hometown for work in the urban while their children stay with their grandparents in rural hometown.…”
Section: Introductionmentioning
confidence: 99%